Evidence for a Transport-Trap Mode of Drosophila melanogaster gurken mRNA Localization. - Lan, L.; Lin, S.; Zhang, S.; Cohen, R.S. (PLoS ONE, 2010)
The Drosophila melanogaster gurken gene encodes a TGF alpha-like signaling molecule that is secreted from the oocyte during two distinct stages of oogenesis to define the coordinate axes of the follicle cell epithelium that surrounds the oocyte and its 15 anterior nurse cells. Because the gurken receptor is expressed throughout the epithelium, axial patterning requires region-specific secretion of Gurken protein, which in turn requires subcellular localization of gurken transcripts. The first stage of Gurken signaling induces anteroposterior pattern in the epithelium and requires the transport of gurken transcripts from nurse cells into the oocyte. The second stage of Gurken signaling induces dorsovental polarity in the epithelium and requires localization of gurken transcripts to the oocyte's anterodorsal corner. Previous studies, relying predominantly on real-time imaging of injected transcripts, indicated that anterodorsal localization involves transport of gurken transcripts to the oocyte's anterior cortex followed by transport to the anterodorsal corner, and anchoring. Such studies further indicated that a single RNA sequence element, the GLS, mediates both transport steps by facilitating association of gurken transcripts with a cytoplasmic dynein motor complex. Finally, it was proposed that the GLS somehow steers the motor complex toward that subset of microtubules that are nucleated around the oocyte nucleus, permitting directed transport to the anterodorsal corner. Here, we re-investigate the role of the GLS using a transgenic fly assay system that includes use of the endogenous gurken promoter and biological rescue as well as RNA localization assays. In contrast to previous reports, our studies indicate that the GLS is sufficient for anterior localization only. Our data support a model in which anterodorsal localization is brought about by repeated rounds of anterior transport, accompanied by specific trapping at the anterodorsal cortex. Our data further indicate that trapping at the anterodorsal corner requires at least one as-yet-unidentified gurken RLE.